2020
DOI: 10.4209/aaqr.2020.01.0005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Residential Woodsmoke PM2.5 in the Adirondacks of New York

Abstract: Although woodsmoke from residential wood heating can be the dominant source of winter PM 2.5 in rural areas, routine monitoring is done primarily in urban or suburban areas. To obtain data on elevated woodsmoke concentrations from nearby sources, the PM 2.5 , black carbon at 880 and 370 nm, particle-bound polycyclic aromatic hydrocarbons (PAHs), and wind speed and direction were measured during winter at three residential locations in Saranac Lake, New York. A paired-site design enabled the identification of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…A mixture of organic and inorganic particles (OC-IN) appears to be the dominant class across all samples, contributing 40 %-76 % to the total particle population. Furthermore, the consideration of multiple sources of EC from wildfires (Park et al, 2007), residential wood smoke (Allen and Rector, 2020), agricultural burning (Liu et al, 2016;Holder et al, 2017), and urban emissions (Paredes-Miranda et al, 2013) in North America led us to expect a large contribution of EC within our sample. However, OC-EC and OC-EC-IN particles contributed only 0.4 %-1.3 % to the total particle population.…”
Section: Internal Mixing Of Individual Particlesmentioning
confidence: 93%
“…A mixture of organic and inorganic particles (OC-IN) appears to be the dominant class across all samples, contributing 40 %-76 % to the total particle population. Furthermore, the consideration of multiple sources of EC from wildfires (Park et al, 2007), residential wood smoke (Allen and Rector, 2020), agricultural burning (Liu et al, 2016;Holder et al, 2017), and urban emissions (Paredes-Miranda et al, 2013) in North America led us to expect a large contribution of EC within our sample. However, OC-EC and OC-EC-IN particles contributed only 0.4 %-1.3 % to the total particle population.…”
Section: Internal Mixing Of Individual Particlesmentioning
confidence: 93%
“…A 330 mixture of organic and inorganic particles (OC-IN) appears to be the dominant class across all samples, contributing 40-76% to the total particle population. Furthermore, the consideration of multiple sources of EC from wildfires (Park et al, 2007), residential wood smoke (Allen and Rector, 2020), agricultural burning (Liu et al, 2016;Holder et al, 2017), and urban emissions (Paredes- Miranda et al, 2013) in North America led us to expect large contribution of EC within our sample. However, OC-EC and OC-EC-IN particles contributed only 0.4-1.3% to the total particle population.…”
Section: Internal Mixing Of Individual Particlesmentioning
confidence: 89%
“…Clearly, woodsmoke concentrations can vary over quite short distances. Allen and Rector conducted a rural study in the Adirondacks of NY . They found that increases in concentrations were mainly driven by local sources, as demonstrated by the lack of correlation of the paired sites used in the study.…”
Section: Impacts Of Biomass Burning On Air Quality In Developed Count...mentioning
confidence: 99%